Study on wettability of water stemming for blasting dust adjusted by surfactants and inorganic salts - Fengjie Chen; Zejun Zhou; Ying Liang; Xiaowen Liu; Xiaoguang Wang; Pu Wang; Bolei Chen; Yong Liang; Yawei Wang (Royal Society Open Science)
Water stemming is an efficient method of removing blasting dust by wetting. There is still a lack of methods for rapid optimization of water stemming components with high wettability. Herein, blasting dust was collected from a tunnel in Chongqing (China) to investigate its removal performance by different water stemmings. The two most important components of blasting dust were SiO2 and CaCO3 by characterization analysis. Notably, hydrophilic blasting dust has significantly more SiO2 than hydrophobic blasting dust. The density functional theory calculation predicted the wettability of water stemming containing sucrose fatty acid ester (SE) higher than that of water stemming containing other surfactants. Moreover, the water contact angle and surface tension experiments determined the addition of inorganic salts to the water stemming containing SE could increase its wettability, with the addition of Al3+ giving the best performance. The sink test and water retention experiment further prove that our synthesized water stemming has a good wetting ability on both hydrophobic and hydrophilic blasting dust. The findings of this study advance the development of reliable methods for optimizing water stemming with high wettability for removing the blasting dust.